The impact of changes in contextual factors on performance management systems in South African universities: a case study - Gozo, Daniel (My University, 2018)
The study examines the causal effect of changes in the contextual factors on performance management systems, using a case study with an exploratory and informative approach. In-depth interviews were corroborated by analysis of annual reports over a period of ten years. Unique performance management systems in use within the university provide a counter-point to the private sector orientation of conventional research in performance management systems and management accounting practices conducted largely in developed economies which has paid insufficient attention to the complexities of the environments within which change occurs. The findings indicate that portability of performance management practices from the private sector to public institutions is questionable when the background of organisations is not being taken into account. Backgrounds of organisations in emerging economies and the external variables and changes thereof need to be considered in understanding management accounting changes. Strong staff unions were found to impact the interplay with external forces of globalisation, competitive forces of declining funding, university ranking league tables, technology, and regulatory changes which affected performance management practices, putting organisational effectiveness at risk. Unique practices such as quinquennial reviews and financial models which derive faculty bottom lines were impacted by change during the decade and should not be ignored or underestimated in considering the bouquet of management control practices essential for meeting organisational objectives. The study also suggests directions which future research in the area of change in management accounting practices could take.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Commerce, 2018
Keywords: Performance--Management; Employee motivation--South Africa